Student and Staff Expectations and Experiences : final report of the project, A Collaborative Multi-Faceted Approach to Address the Gaps Between Student Expectation and Experience at University. - Brinkworth, Russell; McCann, Ben; Burke da Silva, Karen; King, Sharron; Luzeckyj, Ann; McCann, Jacqui; Palmer, Edward (Office for Learning and Teaching, 2014)
Addressing the mismatch between students' expectations of university, and their experiences once they commence, has important ramifications for student satisfaction and, ultimately, retention. By bringing together three participating universities and a number of SA secondary schools, this project will make a substantial contribution to this important issue. By gathering opinions of students, school teachers, and lecturers of first-year students, all points of view will be explored. This is the final report from a project that tracked students as they progressed through their transition year, and compared university entrance scores with student expectations, experiences, grades, transfers, and attrition rates. This thorough analysis of transition will make it the most comprehensive investigation of its type. Furthermore, the creation of an interactive university expectations and experiences website, school visits by both academic and professional staff, and possible changes to university activities, will help disseminate the findings of this work to the people who need it most: potential and commencing university students.